Precipitation oxygen isotope variability across timescales in East Asia records two sub-processes of summer monsoon system - Zhaowei Jing; Zhengyu Liu; Shaoqing Zhang; Qin Wen; Chengfei He; Yuntao Bao; Wusheng Yu (Communications Earth & Environment)
Abstract The seasonal variation of precipitation isotopes (δ18Op) exhibits a north-south dipole in the East Asian monsoon region, correlating with temperature in northern China and precipitation in southern China. However, on longer timescales, δ18Op tends to exhibit spatial coherence. This inconsistency in δ18Op variability across different timescales has sparked considerable debate regarding their climatic interpretation. Here we develop a unified framework to quantify the mechanisms driving δ18Op variability across timescales using water tagging experiments in iCAM5.3 numerical model. Our results demonstrate that δ18Op variations are governed primarily by monsoon-driven changes in moisture source and enroute depletion, rather than local meteorological factors. Furthermore, the relative importance of these processes differs across timescales. Therefore, the evolution of the East Asian summer monsoon, as recorded in δ18Op, should be interpreted through the lens of these two sub-processes of the monsoon system, rather than based solely on the empirical isotopic effects observed on seasonal timescales.